Addressing the barriers to telemedicine utilization for diabetic retinopathy screening in high-risk and underserved population in the United States - Nnamdi Elem Okore (The Pan-American Journal of Ophthalmology)
Diabetic retinopathy (DR) is one of the leading causes of preventable blindness in the United States, among people with diabetes. It develops slowly and often without apparent symptoms in early stages, so detection is essential to avoid vision loss. Still, timely screening for DR remains an issue mainly among poor and rural populations or economically disadvantaged populations who have limited access to routine eye care. The answer to these challenges may be telemedicine which involves remote screening and diagnostic testing for patients who would otherwise not have had access to eye care. By using digital technology to transmit captured retinal images to specialists for analysis, telemedicine allows early detection and treatment of DR without patients travelling long distances, thereby increasing accessibility and improving health outcomes. Telecommunications have helped improve DR screening rates, but there are challenges that it faces today. The main barriers to telemedicine-based DR screening adoption are limited access to technology and digital literacy, patient confidentiality and data security, regulatory variability, and image quality. Based on current literature, policy analyses, and case studies, this review offers evidence-based strategies to overcome these barriers including investments in telehealth infrastructure and equipment’s, digital literacy promotion, standardization of regulatory frameworks, and cross-sector collaboration. By identifying these barriers and finding ways to mitigate them, this review demonstrates how telemedicine can close the eye care gap and promote equity in rural and underserved areas in the United States.